2015
DOI: 10.1111/jnc.13020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the deleterious effects of binge drinking‐like alcohol exposure in adolescent and adult mice

Abstract: A major cause of alcohol toxicity is the production of reactive oxygen species generated during ethanol metabolism. The aim of this study was to compare the effect of binge drinkinglike alcohol exposure on a panel of genes implicated in oxidative mechanisms in adolescent and adult mice. In adolescent animals, alcohol decreased the expression of genes involved in the repair and protection of oxidative DNA damage such as atr, gpx7, or nudt15 and increased the expression of proapoptotic genes such as casp3. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 50 publications
2
24
2
Order By: Relevance
“…Second, we did not measure blood ethanol concentrations (BEC) in the present study. However, two other studies failed to detect age-related differences in ethanol clearance in this strain at 20–30 min after ethanol administration (the interval between injection and the light pulse in our study; (Hefner and Holmes, 2007, Linsenbardt et al, 2009), while a third study reported no age difference in BEC at all (Lacaille et al, 2015). A third limitation is that only photic phase-delays were examined in this report, because adult mice typically show only small advances to light.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Second, we did not measure blood ethanol concentrations (BEC) in the present study. However, two other studies failed to detect age-related differences in ethanol clearance in this strain at 20–30 min after ethanol administration (the interval between injection and the light pulse in our study; (Hefner and Holmes, 2007, Linsenbardt et al, 2009), while a third study reported no age difference in BEC at all (Lacaille et al, 2015). A third limitation is that only photic phase-delays were examined in this report, because adult mice typically show only small advances to light.…”
Section: Discussioncontrasting
confidence: 76%
“…During adolescence, mice of this strain consume more alcohol than adults, particularly in models of limited access, intermittent access, and binge-drinking (Holstein et al, 2011, Melendez, 2011, Moore et al, 2010, Quoilin and Boehm, 2016; but see also Hefner and Holmes, 2007). Adolescent C57BL/6J mice also show differential sensitivity to acute ethanol, including increased sensitivity to ethanol-induced locomotor stimulation (Hefner and Holmes, 2007, Melon and Boehm, 2011), anxiolysis (Hefner and Holmes, 2007), and certain memory impairments (Lacaille et al, 2015, Spanos et al, 2012), and decreased sensitivity to ethanol-induced conditioned taste aversion (CTA; (Holstein et al, 2011, Moore et al, 2013), sedation (Hefner and Holmes, 2007, Linsenbardt et al, 2009), hypothermia and locomotor suppression (Lopez et al, 2003). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BD effects are correlated with cognitive damage in young people as abusive EtOH consumption can have deleterious effects on the adolescent brain (Lacaille et al . ). It causes a significant loss of hippocampal neurons, astrocytes and microglia (Oliveira et al .…”
Section: Introductionmentioning
confidence: 97%
“…Also, results have demonstrated that chronic antidepressant treatment significantly increased neuronal proliferation in the adult DG (Malberg et al 2000), and anxiety induced by stress and depression-like conditions in animal models are associated with reduced DG proliferation (Czeh et al 2001). Furthermore, multiple binge ethanol exposure substantially reduced neurogenesis in the DG of adolescent mice (Lacaille et al 2015). Also, moderate alcohol consumption reduced the number of cells produced in the DG by nearly 40% (Anderson et al 2012).…”
Section: Introductionmentioning
confidence: 91%